Nutritional Guidelines for Patients with Type 1 Diabetes Mellitus and its Adherence- A Narrative Review - Anu Kaushik; Tejmeet K. Rekhi; Seema Puri; Nikhil Tandon (Indian Journal of Endocrinology and Metabolism)
Nutritional guidelines are of importance in directing food choices of T1D patients. The objective is to summarise existing nutritional recommendations and examine its adherence by T1D patients. Literature was searched on dietary guidelines in T1D using electronic databases PubMed, Science Direct, Scopus, Google Scholar, in English and 29 papers were selected. As per ADA, EASD, ISPAD, and ICMR guidelines, energy recommendations for T1D are based on ideal body weight to prevent overweight and obesity. The safe amounts of carbohydrates, protein and fat includes 50–55%, 15–20% and 25–30% of total energy respectively with fiber intake recommended at 20–30 g/day. Vitamin and mineral supplementation are beneficial in the presence of deficiency. Adherence to nutritional recommendations was suboptimal but better in those who were frequently consulting a dietician. As suboptimal dietary adherence leads to poor glycaemic control, nutritional guidelines must be followed to manage T1D and prevent or delay diabetic complications.